في ترشيد التكاليف البيئية ABC تطبيق اسلوب الكلفة على اساس النشاط: بحث تطبيقي في شركة تعبئة الغاز (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of the research is to use methods based on cost-based activities )ABC) to identify the activities that cause the costs resulting from the environmental impact of the gas filling company and then to manage on the basis of the activities to manage the costs of these activities, which in turn rationalizes the environmental costs by eliminating activities that do not add .The research a number of conclusions, the most important of which is that the management of the company should continuously seek to train and qualify its staff on the accounting systems, especially in the field of accounting of environmental costs, the high environmental costs by the company, bears as a result of its activity.